Palambrio: una palabra “lusitana” actual derivada de la raíz *pala-, “piedra” - Almagro-Gorbea, Martín (Estudos Arqueológicos de Oeiras, 2014)
Analysis of the word “pala” and derivative voices kept alive in Spanish and in Galaico-Portuguese language and in the place names of the Galician-Lusitanian region and of the provinces of León, Zamora and Salamanca (Spain). Its meaning as “rock” is confirmed, as its origin in the i.e. Lusitanian language. It thus provides an interesting example of survivals of longue durée in words of prehistoric origin preserved in the western lands of Iberia.